Evaluation of optimizing Monteggia fracture-dislocation care: surgical innovations, radiological insights, and functional rehabilitation in adult patients - Al-Maruf, M. Abdullah; Islam, Shahidul; Asaduzzaman, M.; Hasan, M. Mainul; Hoque, M. Zahidul; Mollick, Raju (International Journal of Research in Orthopaedics, 2024)
Background: Monteggia fractures, rare in adults, involve proximal ulna fracture and radial head dislocation. Managing these injuries poses challenges, fueling historical debates and driving advancements in internal fixation. Watson Jones' frustration highlights the ongoing pursuit of effective surgical approaches for optimal outcomes and functional limb restoration. his study aims to evaluate Monteggia fracture-dislocation treatment by analyzing radiological outcomes for structural insights and alignment post-surgery. Methods: This prospective observational study, conducted at Swapno general hospital, Mirpur-2, Dhaka, Bangladesh from 1st January 2021 to 31 January 2024, enrolled 30 patients with radiologically confirmed Monteggia fracture-dislocation. Surgical procedures involved creating an interval, anatomical reduction, and fixation, with regular follow-ups assessing outcomes, including range of motion, X-rays, and VAS scores, while statistical analysis utilized SPSS version 23. Results: The highest frequency percentage in the age distribution was observed among individuals aged 41-45, constituting 20% of the total sample, while the lowest frequencies were recorded in the 31-35 and >51 age groups, each representing 10% of the sample. Physical assault emerged as the leading cause of injury, accounting for 40% of cases, followed by road traffic accidents at 36.66% and falls at 23.33%. In terms of final outcomes, the majority of patients (43.33%) achieved a good outcome, while the lowest percentage (10%) resulted in poor outcomes. Conclusions: In conclusion, addressing Monteggia fracture-dislocation in adults requires navigating inherent complexities. Modern internal fixation methods prove impactful, emphasizing the need for precise classification and stable anatomical reduction.